Edukasi Pencegahan Judi Online dan Narkoba Terhadap Masyarakat di Jorong Bayang Tengah - Vebri Sugiharto; Lanni Jurriah; Rezky Fauziah Nur; Siti Rodiah Lubis; Abdul Hafis; Ratnasari Dalimunte; Munah Siregar; Asiah Azhari Hasibuan; Muhammad Alwi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Education regarding the prevention of online gambling and drugs is a crucial step in building public awareness of the dangers posed by these two phenomena. Jorong Bayang Tengah, an area with a population consisting mostly of young families and teenagers, is the focus of this prevention effort. This program aims to provide an in-depth understanding of the risks of online gambling and drug abuse, as well as strengthening community social resilience through various educational approaches. The methods used include direct outreach, dissemination of information through print and digital media, as well as interactive discussions involving all elements of society, including traditional leaders, youth and security forces. Through this activity, it is hoped that collective awareness will be created to prevent and fight the practice of online gambling and drug abuse. Initial results from this program show an increase in public understanding of the negative impacts of online gambling and drugs, as well as the emergence of community initiatives to maintain a healthy and safe social environment. It is hoped that this effort can continue on an ongoing basis, so that Jorong Bayang Tengah can become a model for other regions in implementing similar prevention programs.